CFD Simulation to Enhance the Efficiency of Air Compressor - Akhir, Nur Arif Aiman Bin; TS. MOHD FAIZAL BIN ESA (Progress in Engineering Application and Technology, 2021)
The project is about analyze the fluid flow inside the air compressor from one energy to another. For air compressor, the main factor that effect the efficiency is the design of the vane which transfer the amount of energy from the motor to the tank pressure. The simulation analysis of existing air compressor, study can be made to improve the air compressor efficiency on different geometry design. Centrifugal compressor consists of several parts which is impeller, diffuser and volute. One of the critical problems in centrifugal compressor design is the diffuser-impeller interaction. The impeller discharge mixing process appear to be proved experimentally only at low tip speeds, which effect the efficiency. The aim of this project is to study the flow inside the air compressor by analyzing the efficiency of air compressor on different geometry design. All the geometry of the model was generated by using SolidWorks 2017 and the numerical solution was run by ANSYS CFX. At the end of study, impeller design with 10 number of blades and 7 axis ratio edge of blade achieve more performance of efficiency compared to other design. The simulation results can be more precise and more details by adding more lines/point of impeller design during the simulation process. However, the simulation process will be time consuming. Therefore, 5 lines/point of this simulation would be enough to produce good result.